2010
DOI: 10.1007/s11524-009-9427-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Recruitment among Female Sex Workers and Injecting Drug Users at Risk for HIV Using Respondent-driven Sampling in Estonia

Abstract: Few recent publications have highlighted theoretical and methodological challenges using respondent-driven sampling (RDS). To explore why recruitment with RDS may work in some populations and not in others, we assess the implementation of RDS to recruit female sex workers (FSWs) and injection drug users (IDUs) into a human immunodeficiency virus biological and risk behavior survey in Tallinn, Estonia. Recruitment of FSWs was slower and more challenging than that of IDUs. The IDU study recruited 350 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 19 publications
1
32
0
2
Order By: Relevance
“…Due to differences among studies in the definition of drug or injecting networks, network size comparisons are difficult. Keeping this in mind, the mean injecting network size seems to be in line with previous RDS studies of PWID, which have reported mean network sizes of 15-56 [27][28][29]. However, the network size is substantially larger than what has been reported in studies using other sampling methods, such as targeted sampling and service-based sampling, where average drug network sizes of 2.0-5.4 have been reported [30][31][32][33].…”
Section: Discussionsupporting
confidence: 88%
“…Due to differences among studies in the definition of drug or injecting networks, network size comparisons are difficult. Keeping this in mind, the mean injecting network size seems to be in line with previous RDS studies of PWID, which have reported mean network sizes of 15-56 [27][28][29]. However, the network size is substantially larger than what has been reported in studies using other sampling methods, such as targeted sampling and service-based sampling, where average drug network sizes of 2.0-5.4 have been reported [30][31][32][33].…”
Section: Discussionsupporting
confidence: 88%
“…RDS is a variant of the chainreferral method and has been used in several countries, including Brazil (7,(15)(16) . The use of RDS is based on a referral made by peers and requires social networks that connect the target population (7,16) .…”
Section: Methodsmentioning
confidence: 99%
“…The latter enabled us to analyze the characteristics of the investigated population with 95% confidence intervals (CIs) as a function of the recruitment patterns and the network size relative to the other participants, taking the sample homophily and the variable balance reach into consideration (16)(17) . The signs and symptoms of STDs according to the WHO's syndromic approach reported by the interviewees are described in table IV.…”
Section: Methodsmentioning
confidence: 99%
“…We used respondent-driven sampling (RDS) methods [9][10][11][12] that have been subsequently adapted for key populations HIV surveillance and population size estimation purposes [13][14][15][16][17][18][19]. We have described elsewhere how RDS recruitment operated in the SAHMS [2].…”
Section: Sample Size and Precisionmentioning
confidence: 99%